Northpointe Chalet a contemporary retelling of Northanger Abbey - Smith, Debra White (The Jane Austen series, 2018)
When a lively group of customers visit Kathy Moore's café, new friendships--and romance--ensue. When she learns of a mystery in their past, Kathy takes on the role of amateur detective, but will her digging do more damage than good.